Public treasury looting for global North banking, public welfare denial, migration and sex-slave trafficking of Nigerians after colonialism - Ingwe Richard (Bulletin of Geography. Socio-Economic Series, 2014)
Enslaving and victimising the poor by criminals within and outside governments of underdeveloped countries is gaining attention of academics in the social sciences. This article clarifies inter-relationships among modern slavery and trafficking in girls/women for sexual exploitation. It also shows how vulnerability of people victimised by the crime has been increased by policies deriving from neo-liberalism. To facilitate explication of the variables/issues, the study was based on the theoretical/doctrinal and political aspects of neo-liberalism, coinciding with scenarios of declining welfare, increasing susceptibility/vulnerability of Nigeria’s poor (non-elite) and massive unemployed youth to out-migration and traffickers in persons. The explicated issues include modern slavery (generally and trafficking in Nigerian girls/women for sexual exploitation abroad) as well as the relationships among treasury looting and stashing of the loot in the banks of the global North. It is explained how declining welfare (i.e. multiple-dimensional adversities e.g. unemployment) provokes desires in the unemployed to out-migrate and increases their susceptibility to trafficking in persons. Finally, the article is concluded.